PENGARUH UPAH MINIMUM KOTA, PENDAPATAN PER KAPITA, PENDIDIKAN, DAN KESEHATAN TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA: (STUDI KASUS : PERKOTAAN DI PROVINSI ACEH) - Dewi Indah Sari; Ferayanti Ferayanti; Sri Sukma Wahyuni (LPPM Politeknik Pratama, 2025)
This study aims to analyze the impact of the variables of City Minimum Wage, Per Capita Income, Education Level, and Health on the Labor Force Participation Rate in urban areas of Aceh Province. A quantitative approach using panel data is applied in this research, where secondary data is collected from various official sources such as the Department of Manpower, Population Mobility, and the Central Statistics Agency of Aceh Province, covering the period from 2015 to 2024 in five major cities in Aceh. The analyzed variables include City Minimum Wage, Per Capita Income, Average Length of Schooling, and Life Expectancy. The results of this study show that Per Capita Income and City Minimum Wage have a significant positive effect on labor force participation, but not Years of Schooling and Life Expectancy. The results of this study have important implications for policy makers in the design of effective labor and social development policies to increase labor participation in the region. This research is expected to serve as a foundation for the development of labor economics theory and the formulation of sustainable labor development programs in Aceh Province.